2015
DOI: 10.1007/s00394-015-1072-1
|View full text |Cite
|
Sign up to set email alerts
|

Glycaemic responses to liquid food supplements among three Asian ethnic groups

Abstract: Purpose A limited number of studies have compared the glycaemic index (GI) and glycaemic responses (GR) to solid foods between Caucasians and Asians. These studies have demonstrated that Asians have greater GI and GR values for solid foods than Caucasians. However, no study has compared the GI and GR to liquids among various Asian ethnic groups.MethodsA total of forty-eight males and females (16 Chinese, 16 Indians, and 16 Malay) took part in this randomised, crossover study. Glycaemic response to the referenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 11 publications
0
3
1
Order By: Relevance
“…However, all Asian ethnic groups had higher GR compared to Caucasians (albeit not statistically significant) in the order of Malays > Chinese > Indians > Caucasians, except for Malays vs. Caucasians ( p = 0.041). While not completely in line with previous studies [ 4 , 5 , 6 , 20 , 22 ], our findings nevertheless indicate that Asians had a higher GR than Caucasians when a similar amount of carbohydrates were ingested. Since our study recruited populations with comparable age and BMI to previous studies (i.e., relatively young and lean), smaller differences between Asians and Caucasians observed in our study were more likely to be explained by: (1) relatively smaller dose of carbohydrate (CHO) used in our study (50 g vs. 75 g of CHO used in previous study) [ 4 ], and (2) sucrose was selected in our study while glucose was used in the previous study.…”
Section: Discussioncontrasting
confidence: 60%
“…However, all Asian ethnic groups had higher GR compared to Caucasians (albeit not statistically significant) in the order of Malays > Chinese > Indians > Caucasians, except for Malays vs. Caucasians ( p = 0.041). While not completely in line with previous studies [ 4 , 5 , 6 , 20 , 22 ], our findings nevertheless indicate that Asians had a higher GR than Caucasians when a similar amount of carbohydrates were ingested. Since our study recruited populations with comparable age and BMI to previous studies (i.e., relatively young and lean), smaller differences between Asians and Caucasians observed in our study were more likely to be explained by: (1) relatively smaller dose of carbohydrate (CHO) used in our study (50 g vs. 75 g of CHO used in previous study) [ 4 ], and (2) sucrose was selected in our study while glucose was used in the previous study.…”
Section: Discussioncontrasting
confidence: 60%
“…They are either powders which need to be reconstituted to drinks or as ready-todrink formulations, typically containing a balanced mix of energy, protein, fat, and micronutrients [25] [26]. The consumption of the ONSs for people who cannot meet their nutritional requirement has increased over the years [27] [28]…”
Section: Introductionmentioning
confidence: 99%
“…However, with an increasing prevalence of IGT and diabetes in India, it is important to understand the impact of the macronutrient composition of these ONSs on the blood glucose response. While a few studies have previously reported the GI of supplements available in the Indian market [27] [30] [31] [32],…”
Section: Introductionmentioning
confidence: 99%
“…In light of these recommendations and claims, the food industry has focused on developing low GI nutritional formulas or calorie replacers with complete nutritional profiles in different food forms [ 18 , 19 ]. Although liquid nutritional formulas are frequently used by consumers, information on their metabolic consequences, such as GI and II, are limited and rarely compared to solid food [ 12 ].…”
Section: Introductionmentioning
confidence: 99%